Barbara Stanwyck : the miracle woman - Callahan, Dan, 1977- (Hollywood legends series., 2012)
Barbara Stanwyck (1907-1990) rose from the ranks of chorus girl to become one of Hollywood's most talented leading women-and America's highest paid woman in the mid-1940s. Shuttled among foster homes as a child, she took a number of low-wage jobs while she determinedly made the connections that landed her in successful Broadway productions. Stanwyck then acted in a stream of high-quality films from the 1930s through the 1950s. Directors such as Cecil B. DeMille, Fritz Lang, and Frank Capra treasured her particular magic. A four-time Academy Award nominee, winner of three Emmys and a Golden Glo.